Pengaruh Komunikasi Penyuluhan Agama Swadaya terhadap Peningkatan Motivasi Kerja pada Anggota Makoopsud I Jakarta - Rizkulloh, Mochamad Azmi; Prihatini, Rini Laili (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2025)
Abstract: This study aims to analyze the influence of self-reliant religious counseling communication on improving work motivation among members of MAKOOPSUD I Jakarta. The research employs a quantitative approach, involving 80 respondents selected through simple random sampling from a total population of 404 individuals. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression. The findings reveal that self-reliant religious counseling communication significantly influences work motivation. Effective communication, both verbal and non-verbal, enhances understanding of spiritual values and work ethics, ultimately fostering greater enthusiasm and dedication in task execution. Key factors such as message clarity, appropriate communication media, and active involvement of counselors were found to be crucial for the success of this communication. This study is expected to serve as a reference for the development of mental coaching programs in military environments, particularly in enhancing work motivation through spiritual approaches. Furthermore, it provides guidance for self-reliant religious counselors to optimize their communication strategies for greater effectiveness. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh komunikasi penyuluhan agama swadaya terhadap peningkatan motivasi kerja anggota MAKOOPSUD I Jakarta. Penelitian dilakukan menggunakan pendekatan kuantitatif dengan melibatkan 80 responden yang dipilih secara acak sederhana dari total populasi 404 orang. Data dikumpulkan melalui kuesioner berskala Likert dan dianalisis menggunakan regresi linear sederhana. Hasil penelitian menunjukkan bahwa Pola komunikasi berorientasi digunakan oleh penyuluh agama swadaya atau petugas bintal, tingkat singinkasnsi 75,8% terpengaruh oleh komunikasi yang dilakukan, dan pesan yang disampaikan adalah faktor terbesar yang mempengaruhi keberhasilan komunikasi.. Penelitian ini diharapkan dapat menjadi acuan dalam pengembangan program pembinaan mental di lingkungan militer, khususnya untuk meningkatkan motivasi kerja melalui pendekatan spiritual, serta memberikan panduan bagi penyuluh agama swadaya untuk meningkatkan efektivitas strategi komunikasi mereka.